Potentiodynamic behaviour of the rhodium/H2SO4(aq) interface in the potential range of the hydrogen and oxygen electrosorption - Pallotta, C. (1981)
The electrochemical response of Rh/H2SO4(aq) interfaces at 25°C, subjected to different potential—time perturbation programs in the potential range of H and O electrosorption and H and O electrodesorption is reported. The H electrosorption and H electrodesorption involve the participation of at least two distinguishable adsorption states. The degree of reversibility of the corresponding electrochemical processes is appreciably influenced by the history of the electrode including the type of perturbation applied to the electrode in the O electrosorption potential range. The O electrosorption and O electrodesorption involve the formation of different surface species as it is deduced either from the charge balance or from the kinetic response of the electrochemical interface. The early stages of the anodic reaction are interpreted through a reversible charge transfer comprising the formation of OH adsorbed species which later undergoes electrochemical and chemical reactions yielding different O-containing species. The existence of the various O-containing surface species as well as the influence of the most stable ones in the H electrosorption potential range is evidenced through their potentiodynamic electrodesorption. The kinetic results of the O electrosorption are discussed in terms of aging mechanisms including anion adsorption.